2018
DOI: 10.1002/jso.25235
|View full text |Cite
|
Sign up to set email alerts
|

Comparing preoperative imaging modalities in patient selection for breast intraoperative radiotherapy

Abstract: Background This study evaluated the relative accuracy of mammography, ultrasound, and magnetic resonance imaging (MRI) in predicting the tumor size of early stage breast tumors in preoperative selection of patients for intraoperative radiotherapy (IORT). Methods We identified 156 patients with clinical T1/T2, N0 breast cancer who underwent IORT. Clinical, pathologic, and radiation data were collected. The preoperative tumor size obtained by imaging was compared with tumor pathological size. Results The median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This means that MRI is more likely to have contributed to the clinical size determination for tumors in the 60‐ to 120‐ and >120‐day groups. Some have reported that clinical tumor size measured by MRI is better correlated with pathology size than measurements made with mammography or sonography, 18,19 others have found that MRI tends to overestimate size, 20,21 and still others have found sonography and MRI to be comparable 22 . It is unlikely that MRI introduces a systematic bias in one direction or another.…”
Section: Discussionmentioning
confidence: 99%
“…This means that MRI is more likely to have contributed to the clinical size determination for tumors in the 60‐ to 120‐ and >120‐day groups. Some have reported that clinical tumor size measured by MRI is better correlated with pathology size than measurements made with mammography or sonography, 18,19 others have found that MRI tends to overestimate size, 20,21 and still others have found sonography and MRI to be comparable 22 . It is unlikely that MRI introduces a systematic bias in one direction or another.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the findings showed that MRI was the most accurate modality, yielding a tumor diameter that was closest to the final pathology results, although the difference was not statistically significant. May et al, in a study of patients who underwent IORT, found that preoperative MRI was more likely than mammography or ultrasound to overestimate tumor size by at least 0.5 cm. They suggested that otherwise good candidates for IORT should not be ruled out on the basis of MRI findings alone.…”
Section: Discussionmentioning
confidence: 99%